HDAC3 inhibition as a therapeutic strategy in T-cell acute lymphoblastic leukemia via the TYK2-STAT1-BCL2 signaling pathway - Gu, Zhenyang; Liu, Yuchen; Jiao, Yifan; Wang, Hao; Wang, Lili; Le, Ning; Zhang, Xiawei; Liu, Qingyang; Xu, Yang; Liu, Daihong; Gao, Chunji; Dou, Liping (Frontiers in Immunology, 2026)
IntroductionFew advances have been made in the treatment of T-cell acute lymphoblastic leukemia (T-ALL). Approaches targeting histone deacetylases (HDAC) have not been thoroughly investigated in T-ALL. However, the underlying molecular mechanism of HDAC inhibition remains to be fully elucidated.ObjectivesThe study aimed to evaluate the clinical outcome of chidamide (an oral selective HDAC inhibitor for HDAC1, HDAC2, HDAC3, and HDAC10) in combination with chemotherapy in relapsed or refractory T-ALL and explore the underlying molecular mechanism of HDAC inhibition in T-ALL.MethodsThe clinical outcomes of 28 patients with relapsed or refractory T-ALL, who received chidamide in combination with chemotherapy were first evaluated. Chidamide (30mg per dose) was orally administered twice a week for a total of four doses (120mg in total per patient) during the first 2 weeks of the combined salvage chemotherapy. Transcriptomic analysis was used to identify pivotal signaling pathways of histone deacetylase inhibition in T-ALL cell lines. Short hairpin RNA-mediated inhibition, co-immunoprecipitation, and a series of functional assays were performed to verify the putative signaling pathways involved in cell lines, primary patient samples, and mouse models.ResultsOf the 28 patients, 16 achieved a complete response and three achieved a partial response. As an inhibitor of histone deacetylases, chidamide significantly suppressed the proliferation of T-ALL cells and induced apoptosis and cell cycle arrest in vitro. Chidamide treatment significantly inhibited the protein level of HDAC3, but not HDAC1, HDAC2, or HDAC10, in T-ALL cell lines and primary human T-ALL cells. Moreover, the TYK2-STAT1-BCL2 signaling pathway was also substantially inhibited upon chidamide administration. Finally, overexpression of HDAC3 and TYK2 rescued the inhibitory effects of chidamide on T-ALL cells. HDAC3 was found to associate with TYK2 and contributed to activation of the TYK2-STAT1-BCL2 signaling pathway in T-ALL cells.ConclusionOur results highlight the effectiveness of the combination of chidamide and chemotherapy in the treatment of T-ALL patients and suggest that HDAC3 can act as a potential novel therapeutic target to inhibit the TYK2-STAT1-BCL2 signaling pathway in T-ALL.